The Influence of Acculturative Discrepancies on Negative Affect, Drinking to Cope, and Drinking Behavior in Latinas - Ruiz, Michelle (East Carolina University, 2021)
Studies have regularly found that acculturation disproportionality places Latinx women, as compared to Latinx men, at an increased risk for maladaptive drinking behaviors, such as increased drinking frequency, binge drinking, and more frequent episodes of intoxication. While several etiological explanations have been put forward, the relation between acculturation and drinking behaviors in Latinas is not yet fully understood. Thus, the present study sought to evaluate whether acculturative discrepancies, a term used in this study to capture discrepancies in self-perception that may arise as a result of the acculturation process, were predictive of drinking behavior in Latinas. In line with self-discrepancy theory (SDT), two categories of acculturative discrepancies are of interest: 1) acculturative self-discrepancies, which describe a discrepancy between perceptions of one's current acculturation level vs where one ideally wishes to be and 2) acculturative social discrepancies, which describe a discrepancy between perceptions of one's current acculturation level versus the obligations one perceives from friends and parents. More specifically, the present study examined whether acculturative discrepancies were predictive of depressive and anxiety-related symptoms, maladaptive coping mechanisms, and increased alcohol consumption among a sample of 104 college-aged Latinas. Participants were recruited from a research participation subject pool of a large NC university, and completed an online survey regarding acculturative discrepancies, acculturative stress, negative affect, drinking to cope motivation, and drinking behavior. The majority of participants were highly acculturated, 2nd generation immigrants of Mexican American and Puerto Rican background who spoke both English and Spanish. Overall, participants indicated that their current acculturation level was closer to that of their friends than that of their parents, and, notably, this perceived acculturation gap between self and parents was associated with more self-reported depressive symptoms. Moreover, a discrepancy between one's current acculturative level and the level one feels pressured to achieve, based on family expectancies, was associated with drinking to cope with anxiety. However, acculturative discrepancies did not predict drinking behavior. Findings provide preliminary support for distinct acculturative discrepancies between self, friends, and parents, akin to the concept of actual, ideal, and ought selves in SDT, and the potential impact of such discrepancies on Latina's emotional wellbeing. Implications of these findings for research and clinical intervention are discussed.
Keywords: Acculturative Discrepancies; Latinas; Hispanic women; Hispanic American women college students-- Mental health; Hispanic American women college students--Alcohol use; Acculturation; Drinking behavior